A Re-Evaluation of the Grievance Studies Affair - Geoff G. Cole (Humanities, 2023)
During 2018, three academics employed what they referred to as “reflective ethnography” to examine the hypothesis that many disciplines (e.g., sociology, educational philosophy, and critical race theory) are motivated by extreme ideologies, as opposed to generating knowledge. The authors published, or had accepted, seven “hoax” articles in a number of peer-reviewed journals. When the story broke in the Wall Street Journal, the authors stated that the articles advocated a number of ludicrous, inhumane, and appalling ideas. For example, one argued that men should be trained like dogs with shock collars. Their acceptance for publication was therefore taken as evidence for the kind of ideas that many academic disciplines will advocate. In the present article, I will show that the central aspects of the hoax articles do not match with how they were later described by the hoax authors and many other commentators (e.g., journalists). Despite the vast amount of media coverage, this has (virtually) gone unnoticed. I will suggest that the widely accepted narrative of the so-called Grievance Studies affair is incorrect.